HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG MAKROSOMIA DENGAN POLA NUTRISI SELAMA HAMIL TAHUN 2011 - Trisnasiwi, Agil; Trisnawati, Yuli; ., Sumarni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2012)
Which one of the labor trouble is because the passanger, where the baby weights more than 4000 grams. It is call Macrosomia. Sambirata is the one of villages that has large contribution 25% of the Macrosomia labor in January until December 2010 period. The objectives research is to determine the corellation between pregnant women knowledge about Macrosomia with the pattern of nutrition during pregnancy.Â  The research method used analitical corellation study with cross sectional design. The independent variable is pregnant women knowledge of Macrosomia and the dependent variable is the pattern of nutrition during pregnancy. The data collecting instrument used questionnaire. The number of sample in this study were 34 women in TM II and III pregnancy with total sampling. The data analyzed with the rank spearmen. The result is the knowledge of pregnant women about macrosomia in Sambirata is the most unfavorable as many as 18 people (52,9%). The pattern of pregnant women nutrition during pregnancy in Sambirata is not good most of as many as 19 people (55,9%). There is relationship between pregnant women knowledge of Macrosomia with the pattern of nutrition during pregnancy with it p = 0,000 and the corellatif close is medium (0,586). And the conclusion is devired from this research is the relationship between pregnant women knowledge of Macrosomia with the pattern of nutrition during pregnancy. It mean better knowledge of pregnant women about Macrosomia the better nutrition patterns of pregnant women during pregnancy. Â  Keywords : Knowledge about macrosomia, Patterns of nutrition, Pregnant women Daftar Pustaka : 25 (1997-2010)